Step * 1 of Lemma poset-extend-unique


1. SmallCategory
2. Cname List
3. name-morph(I;[]) ⟶ cat-ob(C)
4. i:nameset(I) ⟶ c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2}  ⟶ (cat-arrow(C) (L c) (L flip(c;i)))
5. F1 cat-ob(poset-cat(I)) ⟶ cat-ob(C)
6. F2 x:cat-ob(poset-cat(I))
⟶ y:cat-ob(poset-cat(I))
⟶ (cat-arrow(poset-cat(I)) y)
⟶ (cat-arrow(C) (F1 x) (F1 y))
7. let F,M = <F1, F2> 
   in (∀x:cat-ob(poset-cat(I)). ((M (cat-id(poset-cat(I)) x)) (cat-id(C) (F x)) ∈ (cat-arrow(C) (F x) (F x))))
      ∧ (∀x,y,z:cat-ob(poset-cat(I)). ∀f:cat-arrow(poset-cat(I)) y. ∀g:cat-arrow(poset-cat(I)) z.
           ((M (cat-comp(poset-cat(I)) g))
           (cat-comp(C) (F x) (F y) (F z) (M f) (M g))
           ∈ (cat-arrow(C) (F x) (F z))))
8. cat-ob(poset-cat(I)) ⟶ cat-ob(C)
9. G1 x:cat-ob(poset-cat(I)) ⟶ y:cat-ob(poset-cat(I)) ⟶ (cat-arrow(poset-cat(I)) y) ⟶ (cat-arrow(C) (F x) (F y))
10. let F,M = <F, G1> 
    in (∀x:cat-ob(poset-cat(I)). ((M (cat-id(poset-cat(I)) x)) (cat-id(C) (F x)) ∈ (cat-arrow(C) (F x) (F x))))
       ∧ (∀x,y,z:cat-ob(poset-cat(I)). ∀f:cat-arrow(poset-cat(I)) y. ∀g:cat-arrow(poset-cat(I)) z.
            ((M (cat-comp(poset-cat(I)) g))
            (cat-comp(C) (F x) (F y) (F z) (M f) (M g))
            ∈ (cat-arrow(C) (F x) (F z))))
11. F1 L ∈ (name-morph(I;[]) ⟶ cat-ob(C))
12. ∀i:nameset(I). ∀c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2} .
      ((F2 flip(c;i) x.Ax)) (E c) ∈ (cat-arrow(C) (L c) (L flip(c;i))))
13. L ∈ (name-morph(I;[]) ⟶ cat-ob(C))
14. ∀i:nameset(I). ∀c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2} .
      ((G1 flip(c;i) x.Ax)) (E c) ∈ (cat-arrow(C) (L c) (L flip(c;i))))
15. cat-ob(poset-cat(I))
16. cat-ob(poset-cat(I))
17. x1 cat-arrow(poset-cat(I)) y
⊢ (F2 x1) (G1 x1) ∈ (cat-arrow(C) (F1 x) (F1 y))
BY
TACTIC:(All Reduce
          THEN (Assert ⌜∀d:ℕ. ∀x,y:cat-ob(poset-cat(I)). ∀p:cat-arrow(poset-cat(I)) y.
                          ((poset-cat-dist(I;x;y) ≤ d)  ((F2 p) (G1 p) ∈ (cat-arrow(C) (F1 x) (F1 y))))⌝⋅
          THENM (InstHyp [⌜poset-cat-dist(I;x;y)⌝;⌜x⌝;⌜y⌝;⌜x1⌝(-1)⋅ THEN Auto)
          )
          THEN RepeatFor (Thin (-1))
          THEN Assert ⌜∀x,y:cat-ob(poset-cat(I)). ∀p:cat-arrow(poset-cat(I)) y.
                         ((x y ∈ cat-ob(poset-cat(I)))  ((F2 p) (G1 p) ∈ (cat-arrow(C) (F1 x) (F1 y))))⌝
          ⋅}

1
.....assertion..... 
1. SmallCategory
2. Cname List
3. name-morph(I;[]) ⟶ cat-ob(C)
4. i:nameset(I) ⟶ c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2}  ⟶ (cat-arrow(C) (L c) (L flip(c;i)))
5. F1 cat-ob(poset-cat(I)) ⟶ cat-ob(C)
6. F2 x:cat-ob(poset-cat(I))
⟶ y:cat-ob(poset-cat(I))
⟶ (cat-arrow(poset-cat(I)) y)
⟶ (cat-arrow(C) (F1 x) (F1 y))
7. (∀x:cat-ob(poset-cat(I)). ((F2 (cat-id(poset-cat(I)) x)) (cat-id(C) (F1 x)) ∈ (cat-arrow(C) (F1 x) (F1 x))))
∧ (∀x,y,z:cat-ob(poset-cat(I)). ∀f:cat-arrow(poset-cat(I)) y. ∀g:cat-arrow(poset-cat(I)) z.
     ((F2 (cat-comp(poset-cat(I)) g))
     (cat-comp(C) (F1 x) (F1 y) (F1 z) (F2 f) (F2 g))
     ∈ (cat-arrow(C) (F1 x) (F1 z))))
8. cat-ob(poset-cat(I)) ⟶ cat-ob(C)
9. G1 x:cat-ob(poset-cat(I)) ⟶ y:cat-ob(poset-cat(I)) ⟶ (cat-arrow(poset-cat(I)) y) ⟶ (cat-arrow(C) (F x) (F y))
10. (∀x:cat-ob(poset-cat(I)). ((G1 (cat-id(poset-cat(I)) x)) (cat-id(C) (F x)) ∈ (cat-arrow(C) (F x) (F x))))
∧ (∀x,y,z:cat-ob(poset-cat(I)). ∀f:cat-arrow(poset-cat(I)) y. ∀g:cat-arrow(poset-cat(I)) z.
     ((G1 (cat-comp(poset-cat(I)) g))
     (cat-comp(C) (F x) (F y) (F z) (G1 f) (G1 g))
     ∈ (cat-arrow(C) (F x) (F z))))
11. F1 L ∈ (name-morph(I;[]) ⟶ cat-ob(C))
12. ∀i:nameset(I). ∀c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2} .
      ((F2 flip(c;i) x.Ax)) (E c) ∈ (cat-arrow(C) (L c) (L flip(c;i))))
13. L ∈ (name-morph(I;[]) ⟶ cat-ob(C))
14. ∀i:nameset(I). ∀c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2} .
      ((G1 flip(c;i) x.Ax)) (E c) ∈ (cat-arrow(C) (L c) (L flip(c;i))))
⊢ ∀x,y:cat-ob(poset-cat(I)). ∀p:cat-arrow(poset-cat(I)) y.
    ((x y ∈ cat-ob(poset-cat(I)))  ((F2 p) (G1 p) ∈ (cat-arrow(C) (F1 x) (F1 y))))

2
1. SmallCategory
2. Cname List
3. name-morph(I;[]) ⟶ cat-ob(C)
4. i:nameset(I) ⟶ c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2}  ⟶ (cat-arrow(C) (L c) (L flip(c;i)))
5. F1 cat-ob(poset-cat(I)) ⟶ cat-ob(C)
6. F2 x:cat-ob(poset-cat(I))
⟶ y:cat-ob(poset-cat(I))
⟶ (cat-arrow(poset-cat(I)) y)
⟶ (cat-arrow(C) (F1 x) (F1 y))
7. (∀x:cat-ob(poset-cat(I)). ((F2 (cat-id(poset-cat(I)) x)) (cat-id(C) (F1 x)) ∈ (cat-arrow(C) (F1 x) (F1 x))))
∧ (∀x,y,z:cat-ob(poset-cat(I)). ∀f:cat-arrow(poset-cat(I)) y. ∀g:cat-arrow(poset-cat(I)) z.
     ((F2 (cat-comp(poset-cat(I)) g))
     (cat-comp(C) (F1 x) (F1 y) (F1 z) (F2 f) (F2 g))
     ∈ (cat-arrow(C) (F1 x) (F1 z))))
8. cat-ob(poset-cat(I)) ⟶ cat-ob(C)
9. G1 x:cat-ob(poset-cat(I)) ⟶ y:cat-ob(poset-cat(I)) ⟶ (cat-arrow(poset-cat(I)) y) ⟶ (cat-arrow(C) (F x) (F y))
10. (∀x:cat-ob(poset-cat(I)). ((G1 (cat-id(poset-cat(I)) x)) (cat-id(C) (F x)) ∈ (cat-arrow(C) (F x) (F x))))
∧ (∀x,y,z:cat-ob(poset-cat(I)). ∀f:cat-arrow(poset-cat(I)) y. ∀g:cat-arrow(poset-cat(I)) z.
     ((G1 (cat-comp(poset-cat(I)) g))
     (cat-comp(C) (F x) (F y) (F z) (G1 f) (G1 g))
     ∈ (cat-arrow(C) (F x) (F z))))
11. F1 L ∈ (name-morph(I;[]) ⟶ cat-ob(C))
12. ∀i:nameset(I). ∀c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2} .
      ((F2 flip(c;i) x.Ax)) (E c) ∈ (cat-arrow(C) (L c) (L flip(c;i))))
13. L ∈ (name-morph(I;[]) ⟶ cat-ob(C))
14. ∀i:nameset(I). ∀c:{c:name-morph(I;[])| (c i) 0 ∈ ℕ2} .
      ((G1 flip(c;i) x.Ax)) (E c) ∈ (cat-arrow(C) (L c) (L flip(c;i))))
15. ∀x,y:cat-ob(poset-cat(I)). ∀p:cat-arrow(poset-cat(I)) y.
      ((x y ∈ cat-ob(poset-cat(I)))  ((F2 p) (G1 p) ∈ (cat-arrow(C) (F1 x) (F1 y))))
⊢ ∀d:ℕ. ∀x,y:cat-ob(poset-cat(I)). ∀p:cat-arrow(poset-cat(I)) y.
    ((poset-cat-dist(I;x;y) ≤ d)  ((F2 p) (G1 p) ∈ (cat-arrow(C) (F1 x) (F1 y))))


Latex:


Latex:

1.  C  :  SmallCategory
2.  I  :  Cname  List
3.  L  :  name-morph(I;[])  {}\mrightarrow{}  cat-ob(C)
4.  E  :  i:nameset(I)  {}\mrightarrow{}  c:\{c:name-morph(I;[])|  (c  i)  =  0\}    {}\mrightarrow{}  (cat-arrow(C)  (L  c)  (L  flip(c;i)))
5.  F1  :  cat-ob(poset-cat(I))  {}\mrightarrow{}  cat-ob(C)
6.  F2  :  x:cat-ob(poset-cat(I))
{}\mrightarrow{}  y:cat-ob(poset-cat(I))
{}\mrightarrow{}  (cat-arrow(poset-cat(I))  x  y)
{}\mrightarrow{}  (cat-arrow(C)  (F1  x)  (F1  y))
7.  let  F,M  =  <F1,  F2> 
      in  (\mforall{}x:cat-ob(poset-cat(I)).  ((M  x  x  (cat-id(poset-cat(I))  x))  =  (cat-id(C)  (F  x))))
            \mwedge{}  (\mforall{}x,y,z:cat-ob(poset-cat(I)).  \mforall{}f:cat-arrow(poset-cat(I))  x  y.
                  \mforall{}g:cat-arrow(poset-cat(I))  y  z.
                      ((M  x  z  (cat-comp(poset-cat(I))  x  y  z  f  g))
                      =  (cat-comp(C)  (F  x)  (F  y)  (F  z)  (M  x  y  f)  (M  y  z  g))))
8.  F  :  cat-ob(poset-cat(I))  {}\mrightarrow{}  cat-ob(C)
9.  G1  :  x:cat-ob(poset-cat(I))
{}\mrightarrow{}  y:cat-ob(poset-cat(I))
{}\mrightarrow{}  (cat-arrow(poset-cat(I))  x  y)
{}\mrightarrow{}  (cat-arrow(C)  (F  x)  (F  y))
10.  let  F,M  =  <F,  G1> 
        in  (\mforall{}x:cat-ob(poset-cat(I)).  ((M  x  x  (cat-id(poset-cat(I))  x))  =  (cat-id(C)  (F  x))))
              \mwedge{}  (\mforall{}x,y,z:cat-ob(poset-cat(I)).  \mforall{}f:cat-arrow(poset-cat(I))  x  y.  \mforall{}g:cat-arrow(poset-cat(I))  y 
                                                                                                                                                    z.
                        ((M  x  z  (cat-comp(poset-cat(I))  x  y  z  f  g))
                        =  (cat-comp(C)  (F  x)  (F  y)  (F  z)  (M  x  y  f)  (M  y  z  g))))
11.  F1  =  L
12.  \mforall{}i:nameset(I).  \mforall{}c:\{c:name-morph(I;[])|  (c  i)  =  0\}  .    ((F2  c  flip(c;i)  (\mlambda{}x.Ax))  =  (E  i  c))
13.  F  =  L
14.  \mforall{}i:nameset(I).  \mforall{}c:\{c:name-morph(I;[])|  (c  i)  =  0\}  .    ((G1  c  flip(c;i)  (\mlambda{}x.Ax))  =  (E  i  c))
15.  x  :  cat-ob(poset-cat(I))
16.  y  :  cat-ob(poset-cat(I))
17.  x1  :  cat-arrow(poset-cat(I))  x  y
\mvdash{}  (F2  x  y  x1)  =  (G1  x  y  x1)


By


Latex:
TACTIC:(All  Reduce
                THEN  (Assert  \mkleeneopen{}\mforall{}d:\mBbbN{}.  \mforall{}x,y:cat-ob(poset-cat(I)).  \mforall{}p:cat-arrow(poset-cat(I))  x  y.
                                                ((poset-cat-dist(I;x;y)  \mleq{}  d)  {}\mRightarrow{}  ((F2  x  y  p)  =  (G1  x  y  p)))\mkleeneclose{}\mcdot{}
                THENM  (InstHyp  [\mkleeneopen{}poset-cat-dist(I;x;y)\mkleeneclose{};\mkleeneopen{}x\mkleeneclose{};\mkleeneopen{}y\mkleeneclose{};\mkleeneopen{}x1\mkleeneclose{}]  (-1)\mcdot{}  THEN  Auto)
                )
                THEN  RepeatFor  3  (Thin  (-1))
                THEN  Assert  \mkleeneopen{}\mforall{}x,y:cat-ob(poset-cat(I)).  \mforall{}p:cat-arrow(poset-cat(I))  x  y.
                                              ((x  =  y)  {}\mRightarrow{}  ((F2  x  y  p)  =  (G1  x  y  p)))\mkleeneclose{}\mcdot{})




Home Index